Constrictive Bronchiolitis and Ulcerative Colitis - Heather Ward; Kendra L Fisher; Ranjit Waghray; Jody L Wright; Sharon E Card; Donald W Cockcroft (Canadian Respiratory Journal)
Pulmonary complications occur in an estimated 0.21% of patients with inflammatory bowel disease. The most common presentation of pulmonary manifestations is large airway disease, such as tracheobronchitis, chronic bronchitis or bronchiectasis. Small airway disease, such as constrictive bronchiolitis or bronchiolitis obliterans with organizing pneumonia, is less frequently reported, and is described as occurring in isolation from large airway disease. A case of a postcolectomy ulcerative colitis in a patient who has both large airway involvement, tracheobronchitis and bronchiectasis, and constrictive bronchiolitis is presented.